EFFECT OF DIETARY COMPOST LEVELS ON PRODUCTION PERFORMANCE, EGG QUALITY AND IMMUNE RESPONSE OF LAYING HENS - M. T. Khan; S. Mehmood; A. Mahmud; K. Javed; Saima; J. Hussain; Y. A. Ditta; M. Waqas (Journal of Animal and Plant Sciences, 2019)
A study was executed to explore the effect of dietary compost level on performance, egg quality, and immune response of laying hens. A total of 150 laying hens (18-week old) were distributed among 5 dietary groups comprising 5 replicates of 6 birds each, under a completely randomized design (CRD). The experimental diets consisted of increasing levels of compost (0. 2.5, 5, 7.5, and 10%), with each diet being iso-caloric and iso-nitrogenous. The recorded data were analyzed by one-way ANOVA under CRD. Hen performance parameters, including feed consumption, body weight, egg production, egg weight, egg mass, feed efficiency, livability, and uniformity percentage, were not affected (P > 0.05) by the level compost supplement included in the diet. Although, birds fed the diet containing 10% compost exhibited slightly lower egg production and egg weight compared to other treatments, statistically these differences were non-significant (P > 0.05). Similarly, egg quality and immune response in birds fed diets with 10% compost were numerically lowest, but no statistical differences were seen across treatment (P > 0.05). Birds fed diets containing compost 10% showed the lowest (P = 0.0001) feed cost per kg egg mass. These data indicate that compost can be utilized in layer rations at up to 10% with no negative effects on performance, egg quality, and immune response. Furthermore, the utilization of compost in layer rations may reduce feed cost per kg egg mass.
Keywords: compost; laying hen; performance; egg quality; immune response